The Importance of Career Development in Increasing Employee Motivation - Nur Ibrizah; Annisa’ Fara Nabila; Ira Safitri (International Conference on Psychology and Education (ICPE), 2023)
Career development is a series of positions or positions occupied by a person during his working life through education and training in the corporate environment, which includes activities to prepare individuals to advance the planned career path. This study has a goal of the importance of career development in increasing employee motivation. The data collection technique in this study was a qualitative method using literature studies. While the analysis technique used in this research is to review six articles about the relationship between career development and work motivation. The results of this study concluded that a positive correlation was found between the two variables evenly in the results of previous studies. Career development is very important in increasing employee motivation. Increasing employee motivation through career development is very beneficial for employees. With career development, employees will be increasingly encouraged or motivated to work actively and make maximum contributions to the company so that they can achieve the desired position in their careers.